Implementasi Metode Least Significant Bit dan Advanced Encryption Standard pada Aplikasi Steganografi Berbasis Web - Siregar, Nazrivan Ibrahim; Samudera, Bayu; Panggabean, Romi Okto Rifansah; Fauzan, Ibnu Fauzan (JIKUM: Jurnal Ilmu Komputer, 2026)
Information security is a crucial aspect in the digital era, particularly in data transmission over the internet. In addition to cryptography, steganography serves as an alternative approach that conceals the existence of information itself. This study aims to design and implement a web-based digital steganography application by integrating the Least Significant Bit (LSB) method with the Advanced Encryption Standard (AES) algorithm. The LSB method is used to embed data into digital images by modifying the least significant bits, while AES encrypts the payload prior to embedding. The application is developed using PHP and a web-based interface. The results indicate that the system can embed text messages and document files into digital images without significantly affecting visual quality, and the hidden data can only be extracted using the correct password. Therefore, the integration of steganography and cryptography provides a dual-layer security mechanism for protecting digital information.